Just Culture: Nursing Students Transition to Practice-a Longitudinal Study - Walker, Danielle; Hromadik, Lora; Baker, Manisa; McQuiston, Linda (Nurse educator, 2024)
Although just culture is reportedly integrated across education and practice, little is known about how perceptions may change across time as students transition from prelicensure education to registered nurse in the practice setting. The purpose of this study was to describe and compare just culture perceptions of registered nurses at 2 time points: (1) as prelicensure students and (2) as new graduate nurses with a minimum of 6 months of experience. Utilizing the Just Culture Assessment Tool for Nursing Education (JCAT-NE) and the Just Culture Assessment Tool (JCAT), this within-subject, longitudinal study measured just culture perceptions across time. Although there was no statistically significant change in total scores across time, 8 individual items demonstrated statistically significant change. Students use the knowledge, skills, and attitudes about just culture taught in prelicensure education as new graduate nurses. However, findings reveal areas where the practice environment has altered perceptions of just culture.